The regulatory role of abscisic acid on cadmium uptake, accumulation and translocation in plants - Shen, Chuang; Yang, Yu-Mo; Sun, Ying-Fang; Zhang, Man; Chen, Xiao-Jing; Huang, Ying-Ying (Frontiers in Plant Science, 2022)
To date, Cd contamination of cropland and crops is receiving more and more attention around the world. As a plant hormone, abscisic acid (ABA) plays an important role in Cd stress response, but its effect on plant Cd uptake and translocation varies among plant species. In some species, such as Arabidopsis, Oryza sativa, Brassica chinensis, Populus euphratica, Lactuca sativa and Solanum lycopersicum, ABA inhibits Cd uptake and translocation, while in other species, such as Solanum photeinocarpum and Boehmeria nivea, ABA severs the opposite effect. Interestingly, differences in the methods and concentrations of ABA addition also triggered the opposite result of Cd uptake and translocation in Sedum alfredii. The regulatory mechanism of ABA involved in Cd uptake and accumulation in plants is still not well established. Therefore, we summarized the latest studies on the ABA synthesis pathway and comparatively analyzed the physiological and molecular mechanisms related to ABA uptake, translocation, and detoxification of Cd in plants at different ABA concentrations or among different species. We believe that the control of Cd uptake and accumulation in plant tissues can be achieved by the appropriate ABA application methods and concentrations in plants.